THE IMPACT OF SLANG IN THE USING OF INDONESIAN LANGUAGE FOR YOUNG GENERATION - St. Kuraedah St. Kuraedah St. Kuraedah; Nur Azaliah MAR (Institut Agama Islam Negeri (IAIN) Kendari, 2016)
Slang is the number of words or terms that has special meaning,unique, distorted or even contrary to common sense when used bypeople of a particular subculture. There are concerns that becomesanxiety for observers society of the national language, that are theincreasing of weakening the using of Indonesian standard on most ofthe younger generation caused by the using of language that deviatefrom standard Indonesian, this resulted in the language used becomesnot popular for all ages.Speaking truth will affect the truth of the information submitted.Language does not belong to an individual that can only be used andunderstood by speakers alone, but it would be more appropriate theusing of language when the speaker and hearer understand each otherby well meaning, without having limited by the age limit.Intervention of slang sometimes arise in using Indonesian language inofficial situations that lead to the use of Indonesian mixed with slangand becomes uncommunicative because it can not generally understoodby all people.Regardless of whether or not disrupt of the slang, also has the positiveimpact that with the slang, the adolescents become more creative. Sothat the user does not hurt if it merely enjoy any changes or innovationsemerging language but it must be used in the right situation, the rightmedia and the right conditions.To avoid the use of slang that is very widespread in society in thefuture, the need for efforts at this time to embed and develop anunderstanding and love of the self-generation of the Indonesian as aNational Language. The parents, teachers and the government arehighly demanded their performance in embedding and develop theunderstanding of and love of the children of Indonesia to theIndonesian language. Thus, the use of good and right Indonesianlanguage in the present and in the future may observed. So that the useis not interfere with originality of Indonesian as a language thatunifying the nation.Keywords: Slang, Indonesian language, young generation